Difference in EGFR expression and mean vascular density in normal oral mucosa, oral epithelial dysplasia and oral squamous cell carcinoma. - Alejandra Fernández; Javier Fernández; Maureen Marshall; René Martínez; Sven Niklander; Ziyad S. Haidar (Universidad de Concepción., 2017)
To evaluate the expression of the epidermal growth factor receptor (EGFR) and mean vascular density (MVD) in normal oral mucosa (NOM), oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Material and methods: Descriptive case study. Nineteen histological samples diagnosed with NOM, 18 diagnosed with OED, and 19 with OSCC, were analyzed with immunohistochemistry against EGFR and CD31. EGFR expression was evaluated by extent and intensity of its expression in normal, dysplastic and neoplastic epithelium. MVD was determined through the detection of blood vessels by antibodies against CD31. Results: Extension of EGFR expression was highest in OSCC followed by OED and lowest in NOM, resulting in significant different between the degrees of extension (p<0.001). Intensity of EGFR was similar in NOM, OED and OSCC, without differences in its expression (p=0.533). Differences in MVD were found between NOM and OSCC groups (p<0.01), and between OED and OSCC groups (p<0.01), with no differences between NOM and OED groups (p=0.91). MVD was 21.17±4.98 in NOM, 23.40±5.77 in OED and 33.92±8.39 in OSCC. Conclusion: EGFR is expressed in normal, dysplastic or neoplastic oral epithelium. However, the extent of its expression is greater as malignancy increases. MVD varies according to the diagnosis.